Medical student diversity and the importance of advocacy in choice of career path - Megan Pasquantonio-Pierce; Jessica St. Louis; Emorcia Hill; Amitai S. Miller; Joan Y. Reede; Jeffrey N. Katz (Discover Education)
Abstract Background Medical student demographics have shifted over time, requiring medical schools to engage prospective students from diverse backgrounds. Understanding career motivators may help schools improve recruitment, create inclusive teaching and learning environments, and engage students underrepresented in medicine (UiM). Methods We distributed a cross-sectional survey to two cohorts of first-year students (n = 337) attending a private U.S. medical school. The survey assessed experiences prior to and within the first two years of medical school, motivating factors related to career choice, and demographic characteristics. Results 257 students responded (76% response rate). The responders were 56% male, 40% female, and 4% non-binary or preferred not to report gender. 37% identified as Asian/Pacific Islander, 36% as White, and 21% as UiM. 16% were first-generation to attend college. 45% plan to enter surgical fields, 33% primary care fields, and 22% other fields/subspecialties. Most respondents endorsed the following as extremely or very important for their choice of a career in medicine: intellectual stimulation (96%), helping others (95%), advocating for underprivileged people (78%), and creating new knowledge (74%). UiM responders were statistically significantly more likely than their non-UiM classmates to indicate interest in advocacy for underprivileged populations (OR 4.3, 95% CI 1.4, 12.9). Conclusions Most students indicated that intellectual stimulation, helping others, and creating new knowledge were motivators for entering medical school. However, UiM students are more likely to also cite advocacy as a key motivator. Medical schools should provide curricular and para-curricular offerings that address advocacy and social determinants of health to engage a diverse student body.